Sapo Adat Jojong Sipitu Ethnic Pakpak Semiotic Study - Jekmen Sinulingga; Manro Berutu (International Journal of Law Analytics, 2024)
This title "Sapo Adat Jojong Sipitu Ethnic Pakpak Semiotic Study". Tree from study focuses on Sapo Adat Jojong Si Pitu, with use theory semiotics by Charles Pierce. Study This use method study qualitative, that is something procedure research that produces descriptive data in the form of words, pictures, and not figures , of people or behavior that can observed . Research result This found 23 symbols found in the Sapo Adat Jojong Sipitu among them namely: Jojong Marcaban, Jojong Mbinangun, Gerga Parsulimbat and so on. Every symbol own its function and meaning separately, for example Gerga Perhembun Kumeke own function as ward off aji-aji and its meaning that is protector.